2022
DOI: 10.1002/ijc.34367
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between tumor acidosis, p53 and extracellular matrix regulates pancreatic cancer aggressiveness

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is an extremely aggressive malignancy with minimal treatment options and a global rise in prevalence. PDAC is characterized by frequent driver mutations including KRAS and TP53 (p53), and a dense, acidic tumor microenvironment (TME). The relation between genotype and TME in PDAC development is unknown. Strikingly, when wild type (WT) Panc02 PDAC cells were adapted to growth in an acidic TME and returned to normal pH to mimic invasive cells escaping acidic regions, they d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 54 publications
2
6
0
Order By: Relevance
“…1) Cytoskeleton organization, including microtubules (e.g., TUBB and TUBA1C ), cytoskeleton anchoring ( ACTN4 and EZR ), and cell migration (e.g., MYH9 and ACTG1 ). This is consistent with previous reports showing that pH e substantially affects cell migration and invasion ( 5 , 8 , 29 ).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…1) Cytoskeleton organization, including microtubules (e.g., TUBB and TUBA1C ), cytoskeleton anchoring ( ACTN4 and EZR ), and cell migration (e.g., MYH9 and ACTG1 ). This is consistent with previous reports showing that pH e substantially affects cell migration and invasion ( 5 , 8 , 29 ).…”
Section: Resultssupporting
confidence: 94%
“…Spatiotemporally heterogeneous gradients of oxygen, pH, lactate, other metabolites, and signaling molecules exist in most if not all solid tumors, largely determine the immediate tumor microenvironment (TME), and largely control disease progression (5,6). Work by us and others point to the essential contributions of acidic extracellular pH (pH e ) (6)(7)(8)(9), hypoxia (10), and lactate (11,12) in determining cancer aggressiveness, metastasis, and chemotherapy resistance (7,(13)(14)(15). Differently from each gradient alone, combinations of such gradients determine cancer aggressiveness (16) including cancer stem cell properties (17).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, p53-dependent apoptosis is a well-described mechanism of chemotherapy-induced cancer cell death (Hernández Borrero and El-Deiry, 2021). It is therefore interesting to note thatconsistent with our recent findings in Panc02 mouse pancreatic cancer cells (Czaplinska et al, 2022) the p53KO and -mutant organoids showed a higher baseline viability compared to WT organoids, but lacked the acid-adaptation-induced increase in resistance. In light of previous reports that environmental acidosis elicits p53-dependent cell death, providing a selective growth advantage for cells lacking WT p53 (Williams et al, 1999) the pathway affected may involve downregulation of p53dependent death mechanisms.…”
Section: Discussionsupporting
confidence: 84%
“…At present, there is little data on how acid adaptation changes key phenotypes of cancer cells, including PDAC cells. We recently showed that p53 knockout (KO) exacerbated aggressive growth induced by acid adaptation of Panc02 pancreatic cancer cells in certain extracellular matrix (ECM) conditions (Czaplinska et al, 2022). However, how synergy between acidosis and driver mutations impacts PDAC treatment resistance is fully unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It should also be pointed out that, while, consistent with previous studies, we use the term acid‐ adapted, it is highly likely that the acidosis‐driven event is a selection for those cancer cells that are able to survive the harsh acidic conditions. This is suggested from work from us and others 7 , 38 in which acid‐adapted cells are returned to physiological pH, but a full understanding of the question will require DNA sequencing to study the genetic identity of the populations before and after acid exposure.…”
Section: Discussionmentioning
confidence: 99%